Analysis of HRAS mutations in Japanese patients with oral squamous cell carcinoma - Masahiro Uchibori; Yuko Osawa; Yuuki Ishii; Takayuki Aoki; Yoshihide Ota; Minoru Kimura (Elsevier, 2021)
Objectives: The incidence of oral squamous cell carcinoma (OSCC) is associated with chewing tobacco and heavy consumption of alcohol. OSCC is also associated with Harvey rat sarcoma viral proto-oncogene homolog (HRAS) gene mutations, which are known to be high-risk factors for poor survival outcomes in patients with OSCC. In this study, we analysed HRAS mutations in Japanese patients with OSCC. Methods: Tumours and oral mucosal tissue samples were collected from 84 treatment-naïve patients with OSCC, between April 2010 and November 2012 in the Department of Oral and Maxillofacial Surgery at a university hospital in Japan. Results: An HRAS mutation was identified in one of the 84 tumours (1.2%) using standard Sanger sequencing. This mutation occurred in codon 13 (c.38G > T) of exon 2, and it corresponded to amino acid substitution p.Gly13Val. Statistical analysis demonstrated that HRAS mutations were associated with chewing tobacco (p < 0.05). Consistent with the fact that Japanese people generally do not chew tobacco, the frequency of HRAS mutations among Japanese patients with OSCC was low. Conclusion: Even though HRAS mutations are associated with OSCC, the HRAS gene may be a poor biomarker for investigating OSCC among the Japanese population due to the low frequency of the mutation. This phenomenon may be explained by a relatively low rate of chewing tobacco consumption in this population.